Mutually Best Matches - Hannu Salonen; Mikko A.A. Salonen (Aboa Centre for Economics (ACE), 2016)
We study iterated formation of mutually best matches (IMB) in college admissions problems. When IMB produces a maximal individually rational matching, the matching has many good properties like Pareto optimality and stability. If preferences satisfy a single peakedness condition, or have a single crossing property, then IMB produces a maximal individually rational matching. These properties guarantee also that the student proposing Deferred Acceptance algorithm (DA) and the Top Trading Cycles algorithm (TTC) produce the same matching as IMB. We compare these results with some well-known results about when DA is Pareto optimal, or when DA and TTC produce the same matching.
Keywords: C70; C71; D82; 330; Matching; School choice; College admission